Analysis of the Influence of Bridge Piers on River FlowI-Scouring Calculation. Issue 1 (August 2020) - Deng, Chunyan; Ge, Hua; Long, Rui; Yuan, Yuan
Abstract: Many bridges collapsed due to the affection of flow, among which scouring has become one of the critical reasons that leads to flow-caused bridge damages and accidents, therefore the analysis of pier scour is of great benefit for the safety assessment of bridge engineering. Newly constructed bridges on the Fuhuan River, a tributary of the Yangtze River, are selected as the object of study. The scouring effect of flow on the bridge piers are evaluated, as shown in the calculation results, the existing design scheme can meet the bridge safety requirements.